Mother's Education, Health Practices and Children's Health Needs: A Variance Components Model - Wilcox-Goek, Virginia L. (The Review of Economics and Statistics, 1985)
The association between parents' health practices and children's health requirements is explored in this paper. A variance components model, incorporating unobserved family effects in the estimation procedure, is used. Mother's education is positively related to both children's days of recuperation and visits to medical facilities. Although each of the health practices examined here is significantly related to the mother's education, each health practice is also related to children's health needs independently of mother's education: Good maternal health practices are associated with 1.7 additional days of recuperation and 2.3 additional visits to medical facilities for a child per annum.